Molecular detection of Babesia capreoli and Babesia venatorum in wild Swedish roe deer, Capreolus capreolus. Issue 1 (December 2016) - Andersson, Martin; Bergvall, Ulrika; Chirico, Jan; Christensson, Madeleine; Lindgren, Per-Eric; Nordström, Jonas; Kjellander, Petter
Abstract Background The epidemiology of the zoonotic tick-transmitted parasiteBabesia spp. and its occurrence in wild reservoir hosts in Sweden is unclear. In European deer, several parasite species, includingBabesia capreoli and the zoonoticB. venatorum andB. divergens has been reported previously. The European roe deer, Capreolus capreolus, is an important and common part of the indigenous fauna in Europe, as well as an important host forIxodes ricinus ticks, the vector of severalBabesia spp. in Europe. Here, we aimed to investigate the occurrence ofBabesia spp. in roe deer in Sweden. Findings Roe deer (n  = 77) were caught and sampled for blood.Babesia spp. was detected with a PCR assay targeting the 18S rRNA gene. The prevalence ofBabesia spp. was 52 %, and two species were detected;B. capreoli andB. venatorum in 44 and 7.8 % of the individuals, respectively. Infection occurred both in summer and winter. Conclusions We showed that roe deer in Sweden, close to the edge of their northern inland distributional range, are infected withBabesia spp. The occurrence ofB. venatorum in roe deer imply that it is established in Sweden and the zoonotic implication of this finding should be regarded to a greater extent in future.